Retrospective evaluation of intranasal carcinomas in cats treated with external‐beam radiotherapy: 42 cases. (3rd March 2021) - Yoshikawa, Hiroto; Gieger, Tracy L.; Saba, Corey F.; Fredrickson, Kirsha; Kubicek, Lyndsay; Haney, Siobhan; Ruslander, David; Kelsey, Krista L.; McEntee, Margaret C.; Nolan, Michael W.
Abstract: Background: Little is known regarding the comparative efficacy of various irradiation strategies used to treat intranasal carcinomas (INC) in cats. Objectives: Investigate outcomes and prognostic factors associated with survival for cats with INC. Animals: Forty‐two cats with INC that underwent radiotherapy (RT). Methods: Single‐arm retrospective study. Medical record review for cats with INC that underwent RT at 1 of 7 veterinary RT facilities. Irradiation protocols categorized as: definitive‐intent fractionated RT (FRT), definitive‐intent stereotactic RT (SRT), and palliative‐intent RT (PRT). Median overall survival time (OST) and disease progression‐free survival (PFS; documented by advanced transverse imaging, or recurrence of symptoms) were calculated. Associations between tumor stage, RT protocol/intent, and adjunctive treatment usage and outcome were calculated. Results: Cats underwent SRT (N = 18), FRT (N = 8), and PRT (N = 16). In multivariate modeling, cats received definitive‐intent treatment (DRT; FRT/SRT) had significantly longer median PFS (504 days, [95% confidence interval (CI): 428–580 days] vs PRT 198 days [95% CI: 62–334 days]; p  = 0.006) and median OST [721 days (95% CI: 527–915 days) vs 284 days (95% CI: 0–570 days); p  = 0.001]). Cats that underwent second DRT course at time of recurrence lived significantly longer than cats that received 1 RT course (either DRT or PRT [median OST 824 days (95% CI: 237–1410 days) vs 434 days (95% CI: 277–591 days); p = .028]). Conclusion: In cats with INC, DRT is associated with prolonged OST and PFS as compared to PRT. If tumor progression occurs, a second course of DRT should be considered.